Productive Waqf and Its Management on Bimaristan al-Mansuri During the Period of Sultan al-Mansur Qalawun 1284-1290 - Kusuma, Roihan Fadhil; Badreza, Kholili (El Tarikh : Journal of History, Culture and Islamic Civilization, 2025)
This article aims to analysis the management of productive waqf on Bimaristan al-Mansuri during the reign of Sultan al-Mansur Qalawun. This article is unique and interesting because no yet one has studied about bimaristan in terms of its funding. This article uses the historical method which consists of heuristics, verification, interpretation, and historiography. The approaches and theories used are Islamic philanthropy and productive waqf theory from Mundzir Qahaf. The result of the discussion of this article is that Sultan al-Mansur Qalawun endowed his property in the Egypt and Levant regions in the form of agricultural land, water wells, markets, shops, inns, and baths which were managed using two methods, namely aqad al-ijara (lease contract) and aqad al-ijara al-'amal (lease contract by providing salary/wages). Interestingly, the number of its waqf actually increased in the period after the death of Sultan Qalawun. This was possible because the waqf was managed in a transparent manner, namely the tight separation of authority to manage the finances of the bimaristan between the party who issued the nominal amount of money expenditure (mubashir idara) and the party who disbursed the money expenditure (mubashir sunduq), making the occurrence of fraud and corruption from the bimaristan employees to be minimized, allowing Bimaristan al-Mansuri can be operate to carry out its function as a hospital for centuries.